Possible Lyme Carditis with Sick Sinus Syndrome. (2020) - Cheung, Brian; Lutwick, Larry; Cheung, Michelle
Abstract: Borrelia burgdorferi ( B. burgdorferi ) is a spirochete bacterium that is transmitted via the Ixodes tick. Infection results in Lyme disease with possible cardiac manifestations, which is also known as Lyme carditis. Patients can present with bradycardia due to rapidly fluctuating atrioventricular block (AVB), which is the hallmark of Lyme carditis. However, we present a rare case of sick sinus syndrome (SSS) without AVB in a 47-year-old man with Lyme disease. He initially presented with a headache and subsequently developed new onset bradycardia and a right cranial nerve (CN) VI palsy with diplopia. B. burgdorferi enzyme-linked immunosorbent assay (ELISA) screen and IgM western blot were positive. He was admitted to the intensive care unit. Electrocardiography (EKG) indicated a heart rate in the high 30 s beats per minute (BPM) with several pauses, but no AVB was present. The patient responded well to therapy, and was discharged with an outpatient regimen of doxycycline. Lyme carditis should be considered in patients who develop new onset bradycardia and live in endemic areas.